Perceived social capital and attitudes about liberals and conservatives: A political psychology and community development examination of politically polarized communities. Issue 3 (26th May 2020) - Fisher, Emily L.; Talmage, Craig A.
ABSTRACT: Political groups are often seen as polarized communities. Research suggests social capital predicts intergroup attitudes; those who perceive higher social capital tend to have more positive attitudes about racial outgroups. Do the positive associations between social capital and racial attitudes extend to attitudes about political outgroups? If so, could social capital help reduce political animosities? Lessons are found in the fields of community development and psychology. We conducted a survey ( n = 338) of college students regarding their perceptions of social capital in their university community, as well as their political ideology and attitudes about liberals and conservatives. After controlling for personality and pre-political predispositions, regression analyses indicate asymmetrical effects. Among liberals, social capital positively predicts attitudes about the liberal ingroup and the conservative outgroup. Among conservatives, social capital has no significant effects on attitudes about either political group. Thus, liberals and conservatives respond differently to their beliefs about their communities, potentially impacting the effectiveness of interventions.